Pengaruh Edukasi Gizi melalui Video terhadap Pengetahuan dan Sikap Gizi Seimbang Siswa SMA Negeri 1 Gorontalo - Dita Dwi Aulia Ibrahim; Sunarto Kadir; Vidya Avianti Hadju (Transbahasa, 2026)
Knowledge and attitudes regarding nutrition are important factors that influence adolescents' health. Therefore, nutrition education is an effective strategy to improve individuals' understanding and encourage healthy nutritional practices. This study aimed to examine the effect of video-based nutrition education on knowledge and attitudes toward balanced nutrition among Grade X-2 students at SMA Negeri 1 Gorontalo. This study employed a quantitative approach using a quasi-experimental one-group pre-test and post-test design without a control group. Data were collected over a two-week period through two measurements: a pre-test before the intervention and a post-test after the intervention. The study involved 32 participants. Data were analyzed using the non-parametric Wilcoxon Signed Rank Test. The results showed that the mean knowledge score increased from 11.88 before the intervention to 13.56 after the intervention. Similarly, the mean attitude score increased slightly from 68.06 to 69.06. Statistical analysis indicated a significant effect of the intervention on knowledge (ρ = 0.001, p < 0.05), whereas no significant effect was found on attitudes (ρ = 0.249, p > 0.05). It can be concluded that video-based nutrition education significantly improved students' knowledge of balanced nutrition but did not significantly influence their attitudes. Future studies are recommended to explore the use of other educational media to enhance both knowledge and attitudes toward balanced nutrition.